Novel multifunctional nanocomposite photocatalysts for water remediation applications - Yu, Shuyan (2018)
Recently, semiconductor-mediated heterogeneous photocatalysis has gained recognition as an effective treatment method for the removal of emerging organic contaminants (EOCs). Here, this study synthesized some hybrid multifunctional nanocomposites, such as TiO2-CuS, GO-COOH-CuS, g-C3N4-CuS, GO-COOHCuS-Ag and mpg-C3N4/TiO2, with the aim to explore their water remediation applications, which can reach syngistic effect to show better photodegradation performance than pure semiconductor. In addition, in order to overcome the aggregation and agglomeration of powdered nanoparticle in aqueous solution, GOCOOH-CuS-Ag was coated onto the glass and mpg-C3N4/TiO2 was immobilized into a PSf membrane to explore their water remediation applications. They all showed excellent photodegradation abilities. First of all, TiO2 nanospheres were synthesized and then modified with copper (II) sulfide (CuS) to form TiO2-CuS-a and TiO2-CuS-b respectively by two different loading methods (direct deposition vs. bifunctional linker coupling). The structural, morphological and optical properties of the two different composites TiO2-CuS-a and TiO2-CuS-b were characterized and compared using FESEM, HRTEM, XRD, XPS, BET and DRS techniques. The TiO2-CuS-b with a regular “spiky ball - like” structure exhibited enhanced disinfection ability, improved photodegradation performance of organic pollutants and hydrogen evolution efficiency under solar and UV light as compared to TiO2-CuS-a (direct deposition method) due to its higher effective combination with CuS through the bifunctional linking molecule -L-cysteine. The influence of CuS content, the structure and the charge-transfer mechanism were systematically investigated by PL, CV, EIS and EPR techniques. Because TiO2 only can use the UV light, which accounts to 5% of solar light, so in order to harvest the visible light more efficiently, carboxylic acid functionalized graphene oxide-copper (II) sulfide nanoparticle composite (GO-COOH-CuS) was prepared from carboxylated graphene oxide and copper precursor in dimethyl sulfoxide (DMSO) by a facile synthesis process at room temperature. The high effective combination, the interaction between GO-COOH sheets and CuS nanoparticles, and the enhanced visible light absorption were confirmed by various characterization techniques. The as-synthesized GO-COOH-CuS nanocomposite exhibited excellent photocatalytic degradation performance of phenol and rhodamine B, high antibacterial activity toward E. coli and B. subtilis, and good recovery and reusability. The influence of CuS content, the synergistic reaction between CuS and GO-COOH, and the charge-transfer mechanism were systematically investigated. The facile and low-energy synthesis process combined with the excellent degradation and antibacterial performance signify that the GOCOOH-CuS has a great potential for water treatment application. In addition, using photocatalyst and solar energy to split water into hydrogen is an ideal energy source, and as reported, g-C3N4 showed better hydrogen generation ability than GO. Hereto, a novel hybrid multifunctional g-C3N4-CuS nanocomposite photocatalyst was synthesized for H2 evolution by integrating a g-C3N4 nanosheet with hexagonal CuS nanoplates via a facile hydrothermal method at room temperature. The ultrathin large surface area g-C3N4 nanosheets were prepared by a “green” liquid exfoliation route from bulk g-C3N4 in isopropanol. Different nanostructural g-C3N4 materials were compared and the results confirmed that the g-C3N4 nanosheet had better hydrogen evolution than the bulk material under solar irradiation owing to its larger surface area and higher light absorption efficiency. Furthermore, given the improved charge separation efficiency, the novel nanocomposite g-C3N4-CuS-1 demonstrated much better hydrogen evolution rate (126.5 µmol h-1) than the pure g-C3N4 nanosheet under solar light. Its performance is also superior than of other semiconductor modified g-C3N4 materials, and making it a promising photocatalyst for future hydrogen generation application. The optical properties, crystal phase and morphology of the obtained composites were characterized systematically using various analytical methods. It was concluded that O2•− was the dominant radical for hydrogen evolution through photoluminescence (PL) and electron paramagnetic resonance (EPR) analysis. In addition, in order to overcome the problem from the agglomeration of powdered particles in water, this study explored the photodegradation performance of glass coating and membrane methods for the photodegradation. For glass coating immobilization method, a hybrid multifunctional nanocomposite (GO-COOH-CuSAg) was synthesized via a facile method by integrating copper sulfide (CuS) nanoflakes, carboxylic acid functionalised graphene oxide (GO-COOH) sheets, and silver (Ag) nanoparticles, with the aim to enhance their EOCs photodegradation and antibacterial applications under solar light irradiation. The crystal phase, optical properties and morphology of obtained composite were characterized using various characterization methods. The as-synthesized GO-COOH-CuS-Ag nanocomposites were transformed and applied on glass via a glass coating method aimed at facilitating their practical applications in photodegradation of emerging organic contaminants (EOCs) and disinfection for water treatment under solar light irradiation. The glass coatings had excellent photodegradation and antibacterial performance with good stability and repeatability. It was also found that synergistic reactions existed among CuS, Ag and GO-COOH, and the mechanisms of charge transfer and photo-disinfection were systematically investigated. The results clearly demonstrate its high performance potential in photodegradation and photodisinfection processes with the advantage of simplifying the recovery and reuse in comparison to powdered forms, and reducing problems including the agglomeration of powdered particles that may cause blockages. For membrane immobilization method, a novel mesoporous graphitic carbon nitride/titanium dioxide (mpg-C3N4/TiO2) nanocomposite was successfully synthesized and incorporated into polysulfone (PSf) matrix to fabricate photocatalytic membranes. This study aimed to explore the photocatalytic ability of the novel nanomaterial membrane in degrading the antibiotic sulfamethoxazole (SMX) under solar light. The structural and morphological properties of the mpgC3N4/TiO2 nanocomposite and membrane were characterized using various techniques. The SMX photocatalytic degradation performance, pathway and mechanism by mpg-C3N4/TiO2 photocatalytic membrane reactor (PMR) were systematically investigated using HPLC and LC-MS/MS. As a pharmaceutically active compound, SMX was transformed into 7 kinds of non-toxic and pharmaceutically inactive byproducts by the innovative PMR technology. SMX removal efficiency of the membrane PSf-3 (with 1% mpg-C3N4/TiO2 loading) was the highest over the 30 h consecutive irradiation. Meantime, the membrane didn’t affect the SMX photodegradation, and the structure was able to provide stable support with high integrity and flexibility after solar irradiation. The developed membrane has a great potential to be applied in water treatment industry.